Aspartic Acid as Corrosion Inhibitor of Mild Steel Corrosion Using Weight Loss, Acidimetry and EIS Measurement - Adejo, Sylvester Obaike; Yiase, Stephen Gbaoron; Gbertyo, Joseph Aondoaver; Ojah, Emmanuel Onah (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
Corrosion inhibition characteristics of aspartic acid on mild steel corrosion in 0.5 M H2SO4 was investigated using weight loss, acidimetry, and electrochemical impedance spectroscopy (EIS). Analysis of the metal surface morphology, uninhibited and inhibited, was carried out through scanned electron microscope. The results showed that the inhibition efficiency increased with increase in inhibitors concentration and rise in temperature for all methods used. The highest v efficiency of 32.36 %, 66.26 % and 80.40 % were obtained for weight loss, acidimetry and EIS, respectively. The low value of efficiency for weight loss compared to other methods should signify the limitation for the method. The increase in efficiency with rise in temperature is a feature of chemical adsorption, which was confoirmed by the value of parameter b of the Adejo-Ekwenchi adsorption isotherm (AEI) model. Values of free energy of adsorption, ?Gads were all negative for all the methods, which means the adsorption processes were spontaneous. The heats of adsorption, Qads values were all positive, implying that the processes were endothermic. Values of activation energy were fairly constant, which is an evident to support the proposed chemical adsorption mechanism. The negative sign in the values of entropy of adsorption, ?Sads is an indication that the activated complex in the rate-determining step was associative. The data obtained was tested with several isotherms, but found to best fit into the El-Awady, Freundlich and Tempkin adsorption isotherm models.